The history of science, the ‘big picture’ and the politics of scale - James Poskett; James Poskett (BJHS Themes)
What does it mean to write the history of science and the ‘big picture’? In this introduction, I argue that ‘scale’ is a crucial but relatively underutilized concept for addressing this question. Rather than taking ‘big’ as a transparent category, I develop a detailed theoretical account of scale in the history and historiography of science. Following work in political geography, I argue that there is a ‘politics of scale’, one that the sciences have played a key role in shaping. Following work in the philosophy of history, I argue that scale should be thought of in its temporal dimension as well as its more traditional spatial dimension. And following work in cultural anthropology, I argue that scale should be understood as an actor's category just as much as an analytic category. The sciences, it turns out, have been one of the principal means through which scale is made and contested. More broadly, this volume of BJHS Themes encourages a creative and open-ended approach to scale in the history of science.